The Effect of Product Quality and E-Wom on Purchase Intention Through Customer Trust at Toyota Company - Cilia Yumaiza; Munawar Asikin (MJK PUBLISHER, 2025)
This study aims to analyze the influence of product quality and electronic word of mouth (e-WOM) on purchase intention, with customer trust as a mediating variable in Toyota e-commerce in Indonesia. The study used a quantitative approach with an explanatory survey method. A total of 200 respondents, active users of the Toyota e-commerce platform, were selected using a purposive sampling technique. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with the assistance of SmartPLS 4.0 software. The results showed that product quality and e-WOM had a positive and significant effect on customer trust and purchase intention. Customer trust was shown to act as a significant partial mediator. The research model had strong predictive power with an R² value of 0.612 for customer trust and 0.735 for purchase intention. Customer trust is a key mechanism that bridges the influence of product quality and e-WOM on purchase intention on automotive e-commerce platforms. The practical implications of this research emphasize the importance of an integrated digital strategy that prioritizes transparency of product quality information, active management of online reviews, and sustainable consumer trust building.